RUANG SEHAT DI TENGAH POLUSI: PENERAPAN PURIFIKASI UDARA BERBASIS AIR PADA COMMUNITY HUB DI CAKUNG - Haryono, Bryan; Gandha, Maria Veronica (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
Air pollution is one of the most critical environmental challenges faced by the city of Jakarta, with significant impacts on public health, the economy, and overall quality of life. The largest emissions originate from the transportation sector, followed by industrial activities, construction, and open burning. Vulnerable groups such as children, the elderly, and individuals with respiratory illnesses—especially those living near major roads and industrial zones—are the most affected. This research aims to formulate regenerative architectural design strategies with the goal of creating healthy living environments in response to air pollution. The main focus is directed toward the use of water-based air purification systems as an active solution integrated into building and public space design. The methods used include literature studies, field observations, mapping of high-pollution areas, and design analysis based on air filtration technologies and green open spaces. Expected outcomes include the identification of spatial characteristics of affected areas, the development of architectural design prototypes that function as an air purification media, and contextual design guidelines for dense urban areas in Jakarta. These findings are expected to contribute concretely to addressing the air pollution crisis through the strategic role of architecture in improving the quality of the urban environment. Keywords: air pollution; air purification; health; regenerative Abstrak Polusi udara merupakan salah satu tantangan lingkungan paling kritis yang dihadapi kota Jakarta, dengan dampak signifikan terhadap kesehatan masyarakat, ekonomi, dan kualitas hidup. Emisi terbesar berasal dari sektor transportasi, diikuti oleh aktivitas industri, konstruksi, dan pembakaran terbuka. Kelompok rentan seperti anak-anak, lansia, serta penderita penyakit pernapasan, terutama yang tinggal di dekat jalan utama dan kawasan industri, menjadi yang paling terdampak. Penelitian ini bertujuan untuk merumuskan strategi desain arsitektur regeneratif dengan target menciptakan ruang hidup yang sehat terhadap polusi udara. Fokus utama diarahkan pada pemanfaatan sistem purifikasi udara berbasis air sebagai solusi aktif yang terintegrasi dalam desain bangunan dan ruang publik. Metode yang digunakan mencakup studi literatur, observasi lapangan, pemetaan kawasan dengan tingkat polusi tinggi, serta analisis desain berbasis teknologi penyaring udara dan ruang terbuka hijau. Hasil yang diharapkan meliputi identifikasi karakter spasial wilayah terdampak, pengembangan prototipe desain arsitektur yang berfungsi sebagai media purifikasi udara, serta panduan desain kontekstual untuk wilayah urban padat di Jakarta. Temuan ini diharapkan dapat menjadi kontribusi nyata dalam merespons krisis polusi udara melalui peran strategis arsitektur dalam peningkatan kualitas lingkungan perkotaan.